2022
DOI: 10.1111/jcal.12768
|View full text |Cite
|
Sign up to set email alerts
|

Lesson learned from the pandemic for learning physics

Abstract: Background Valuable safeguards against fast‐spreading conjectures about learning in times of fear and uncertainty are evidence‐based approaches to the assessment of the impact of sudden and unforeseen disruptions on learning practices. The present research focused on physics learning in such times because conceptual and computational literacy in physics is critical to the development of a scientifically and technologically literate society. Objectives The present research aimed (a) to offer an objective assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Because previous studies have shown larger gender gaps in high-stakes than low-stakes assessment [36], and women are more likely to report low self-efficacy [18] and high test anxiety [14,23] than men, we hypothesize that test anxiety and self-efficacy will more strongly predict high-stakes than low-stakes assessment outcomes. Additionally, there is some evidence that remote learning particularly benefits women [37]. Thus, we also predict that the course type with the lowest-stake assessments (for example, more exams or exams in multiple parts) will have smaller gender differences in performance.…”
Section: Introductionmentioning
confidence: 84%
“…Because previous studies have shown larger gender gaps in high-stakes than low-stakes assessment [36], and women are more likely to report low self-efficacy [18] and high test anxiety [14,23] than men, we hypothesize that test anxiety and self-efficacy will more strongly predict high-stakes than low-stakes assessment outcomes. Additionally, there is some evidence that remote learning particularly benefits women [37]. Thus, we also predict that the course type with the lowest-stake assessments (for example, more exams or exams in multiple parts) will have smaller gender differences in performance.…”
Section: Introductionmentioning
confidence: 84%
“…This study is born from the acknowledgment that, by and large, the assessment of the impact of the pandemic on learning has tended to be limited either to the time of the pandemic or to a comparison of the periods before and during the pandemic [7][8][9][10][11]. Furthermore, research on the impact of the pandemic on learning has entailed either a combination of courses, thereby overlooking course specificity in a quest for generalization [12][13][14], or a few courses within specific disciplines [8,9].…”
Section: The Present Studymentioning
confidence: 99%
“…This study is born from the acknowledgment that, by and large, the assessment of the impact of the pandemic on learning has tended to be limited either to the time of the pandemic or to a comparison of the periods before and during the pandemic [7][8][9][10][11]. Furthermore, research on the impact of the pandemic on learning has entailed either a combination of courses, thereby overlooking course specificity in a quest for generalization [12][13][14], or a few courses within specific disciplines [8,9]. Concerning the distinction between the Global North and Global South and its related biases [15], research has been surprisingly inclusive not only of student populations of the Global North but also of the traditionally understudied populations of the Global South [16][17][18][19].…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation